ANALISIS ALGORITMA K-MEANS DALAM PENGELOMPOKAN PERKARA PERCERAIAN BERDASARKAN KELURAHAN DI KOTA JAMBI - Elvi (Jurnal PROCESSOR, 2021)
Getting married and living happily ever after is the hope of both brides when carrying out the wedding. During the household, no one expects a dispute let alone an end to divorce. A number of areas in jambi city based on the Annual Report of jambi Religious Court from 2017, 2018 and 2019 are known that there is an increase in divorce rates reviewed from the number of cases received by the Jambi Religious Court which each year is always increasing. Therefore, it is necessary to know which areas are experiencing an increase in divorce cases by using one of the methods contained in the data mining, namely the k-means clustering algorithm. From the case, the authors conducted a study to group divorce cases by village in jambi city by applying quantitative research methods with a sample of 62 data with the aim of knowing the divorce rate in jambi city in order to provide a solution that is able to map the villages that conduct divorce. The results of this study showed that the highest divorce rate in jambi city for high clusters (C2) as many as 11 villages, for medium clusters (C1) as many as 20 Villages and for low clusters (C0) as many as 30 Villages then the results obtained from data testing on Rapidminer with k-means algorithm obtained results that matched displaying three classes of classification results. Keywords: K-Means, Clustering, Divorce , Marriage, Rapidminer